The Father-adolescent Relationship In Algerian Society - عبد الحق عمار (مجلة دراسات في سيكولوجية الانحراف, 2022)
The purpose of our study is to determine the relationship between the teenage girl with his father in our contemporary Algerian society, this because adolescence is a crucial step in the development of the individual, who prolongs childhood, where the individual is in full tranquility in his body that he ended up perceiving in his multiple dimensions, and ends in adulthood, where the person is considered to have acquired the tools that allow him to integrate the world of Adults. To carry out this study we used the methodology of the case study which is based on the interview in the first place and also on observation, as a result we made interviews with adolescent girls aged 15 to 17, and have done a content analysis of their stories. Upon arrival we managed to conclude that the relationship that the father maintains with his teenage child has indeed evolved and changed, indeed the father is no longer that person distant from his child (teenager), but rather, he became close to him, listening to him.